(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: In the present study, liposomes of sertraline hydrochloride were formulated for use in depression. Materials and Methods: The liposomes were formulated by film hydration technique and were characterized for surface morphology, particle size, drug entrapment, and drug release potential. The antidepressant-like activity was studied using chronic unpredictable mild stress procedure and then further, the responsiveness toward treatment as measured by changes in swimming, immobility, and struggling behavior of rats. Results: Negatively charged liposomes with an average size of 154 nm showed controlled drug release. Behavioral studies on stress-induced rat model showed a significant increase in the swimming and immobility time and a decrease in the struggling behavior of animals in comparison to a marketed sertraline hydrochloride formulation. Conclusions: The antidepressant-like activity was studied using chronic unpredictable mild stress procedure and then further, the responsiveness toward treatment as measured by changes in swimming, immobility, and struggling behavior of rats.